1895. SingHealth COVID-19 Disease Registry. (15th December 2022) - Shoon, Jin Yee; Conceicao, Edwin P; Yang, Yue; Arora, Shalvi; Ong, Eng Hock Marcus; Chan, Sze Ling; Sim, Xiang Ying Jean; Venkatachalam, Indumathi
Abstract: Background: One of Singapore's national strategies for the COVID-19 pandemic was containment. Efforts included a fourteen-day quarantine of close contacts, were subjected to an entry and exit SARS-CoV-2 PCR test, the latter being done between 11-14 days post exposure. Additionally, symptomatic contacts were tested for SARS-CoV-2. We aim to determine the trend in COVID-19 incubation periods during three distinct pandemic waves corresponding to different SARS-CoV-2 variants. Incubation Period Incubation period of the prevalent SARS-CoV-2 variant in circulation Methods: This is an ecological study and information collected from the SingHealth COVID-19 Registry, a database of all inpatients admitted to any of the SingHealth hospitals. For patients under quarantine, the start date of the quarantine period was assumed to be the last date of exposure to the index case. Incubation period was determined by the duration between date of exposure and date of the first positive SARS-CoV-2 PCR test. The prevalent strain in circulation was identified from the Singapore database in the GISAID collection. Only variants of concern, as categorized by WHO, Alpha (23rd Jan 2020 – 1st Mar 2021), Delta (5th May 2021 – 31st Oct 2021) and Omicron (1 st Jan 2022 – Present) were considered. For the Omicron variant, quarantine was discontinued, hence the last date of arrival from international travel was assumed to be the date of exposure. Results: From January 2020 to March 2022, there were 19, 905 patients in the COVID-19 registry, of whom 11, 235 were under quarantine and 8, 612 had preceding international travel. Of the 11, 235 patients under quarantine, 8, 189 patients were infected when SARS-CoV-2 Alpha variant and 3, 046 patients were infected when SARS-CoV-2 Delta variant were in circulation. Of the 8, 612 patients with preceding travel, 6, 503 patients were infected when SARS-CoV-2 Omicron variant was in circulation. The median incubation period for the Alpha variant was 11 days (IQR: 7-14 days) versus 3 days (IQR: 2-4 days) for the Delta variant versus 3 days (IQR: 0-5 days) for the Omicron variant. Pairwise comparisons between the variants were (p-value = < .001) Conclusion: The significant differences between incubation periods of the SARS-CoV-2 variants in circulation poses a challenge to containment efforts and has emphasize the importance of dynamic national strategies. Disclosures: All Authors : No reported disclosures.